(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
The use of telemedicine is rapidly increasing in the last few years. Telemonitoring and televisit services are proved to be effective in home care. The telemedicine project “Guardian Angel” was started in 2014 and then updated in 2019 in the pediatric hospital Santobono-Pausilipon in Naples carries out telemonitoring and televisit activities on home-ventilated pediatric patients. Over the years, the project has seen a remarkable improvement in more aspects. The objective of this work is to give an update on the project, show all the improvements and give a quality measurement approach.